2018
DOI: 10.5604/01.3001.0012.7744
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microbiological Quality of Milk Products From Organic and Conventional Production

Abstract: The aim of the research was to compare the microbiological quality of dairy products derived from organic and conventional farming. The test material consisted of milk and milk products (natural yoghurt, cream, curd cheese, rennet ripening cheese, milk). Investigated products were subjected to microbiological analysis and marked for the number of Enterococcus sp., Staphylococcus aureus, yeast and moulds, Escherichia coli as well as to state the presence of Salmonella sp. in them. All samples were free of Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The total bacterial count (TBC) is the second important parameter of milk hygiene. The number and types of microorganisms in milk immediately after milking are affected by milking hygiene (cleanliness of milking equipment and access to water) [70][71][72][73]. Total bacterial count is a good indicator for monitoring sanitary conditions during the production and handling of dairy products.…”
Section: Microbiological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…The total bacterial count (TBC) is the second important parameter of milk hygiene. The number and types of microorganisms in milk immediately after milking are affected by milking hygiene (cleanliness of milking equipment and access to water) [70][71][72][73]. Total bacterial count is a good indicator for monitoring sanitary conditions during the production and handling of dairy products.…”
Section: Microbiological Qualitymentioning
confidence: 99%
“…Therefore, they recommended that producers of curd cheeses should lower the storage temperature of these cheeses to below 4 • C, which would minimize microbial growth and ensure the high quality of the cheese. In another Polish study by Kukułowicz [72] concerning pasteurized milk (2%) and dairy products (natural yoghurt, cream, cottage cheese, and ripened rennet cheese), whose main ingredient was pasteurized cow milk (58 products in total), Salmonella spp. bacteria were not found in any of the samples tested.…”
Section: Microbiological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Haskell et al (17) detected S. aureus at a higher level in raw poultry meat from conventional farms (27.4%) than in this meat from antibiotic-free farms (13%). Also in the case of dairy products, the percentage of S. aureus-positive samples was higher for the non-organic (44.8%) than for the organic products (31%) (30). There are also studies that demonstrated the complete absence of S. aureus in livestock raised in an ecology and welfare-promoting system (10).…”
Section: Contamination With Staphylococcus Aureusmentioning
confidence: 99%